2017
DOI: 10.1039/c7md00052a
|View full text |Cite
|
Sign up to set email alerts
|

Histone lysine methyltransferase structure activity relationships that allow for segregation of G9a inhibition and anti-Plasmodium activity

Abstract: We identify key SAR features which demonstrate that high parasite vs. G9a selectivity can be achieved for the quinazoline inhibitor chemotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 72 publications
1
30
0
Order By: Relevance
“…Thus, compound 17 was directly reacted with sodium methoxide to afford compound 21 in 51% yield, followed by demethylation to produce dihydroisoquinoline-1,3-dione 20 with a high yield of 93%. 31 In order to convert 20 to the key intermediate 12, we explored many reagents, such as PCl 5 , POCl 3 , SOCl 2 and PhPOCl 2 , it turned out that PhPOCl 2 behaved the best yield with 47%. 31 The key intermediate 12 reacted smoothly with hydroxyacetal under alkaline conditions to give compound 10 with high yield (98%), 32 and then 10 reacted with various arylboronic acids containing a benzyloxy structure to produce 22 in yields ranging from 46% to 98%.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, compound 17 was directly reacted with sodium methoxide to afford compound 21 in 51% yield, followed by demethylation to produce dihydroisoquinoline-1,3-dione 20 with a high yield of 93%. 31 In order to convert 20 to the key intermediate 12, we explored many reagents, such as PCl 5 , POCl 3 , SOCl 2 and PhPOCl 2 , it turned out that PhPOCl 2 behaved the best yield with 47%. 31 The key intermediate 12 reacted smoothly with hydroxyacetal under alkaline conditions to give compound 10 with high yield (98%), 32 and then 10 reacted with various arylboronic acids containing a benzyloxy structure to produce 22 in yields ranging from 46% to 98%.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
“…31 In order to convert 20 to the key intermediate 12, we explored many reagents, such as PCl 5 , POCl 3 , SOCl 2 and PhPOCl 2 , it turned out that PhPOCl 2 behaved the best yield with 47%. 31 The key intermediate 12 reacted smoothly with hydroxyacetal under alkaline conditions to give compound 10 with high yield (98%), 32 and then 10 reacted with various arylboronic acids containing a benzyloxy structure to produce 22 in yields ranging from 46% to 98%. 19 Finally 22 were cyclized under acidic conditions to give a series of dihydrooxazolo[2,3-a]isoquinolinium analogues (Scheme 5, compounds 23d-23o in Fig.…”
Section: Synthetic Proceduresmentioning
confidence: 99%
“…H3K9me marks), and are also hypothesised to be promising drug targets (16), with BIX01294 (as model HKMT inhibitor, HKMTi) successfully inhibiting asexual P. falciparum proliferation and gametocyte viability (15,16). The diaminoquinazoline chemotype has shown to be particularly effective HKMTi against asexual P. falciparum parasites, with diversity set screens resulting in selective inhibitors identified (15,16,19). Although these data support the notion that epigenetic modulators could be drug targets in parasite development as well as differentiation, some chemotypes show overt toxicity, poor selectivity and sometimes poor pharmacokinetics (31).…”
Section: Introductionmentioning
confidence: 98%
“…The parasite's genome encodes a unique complement of histone modifying enzymes including histone deacetylases (HDACs), histone acetyltransferases (HATs), histone methyltransferases (HMTs, including lysine HKMT), protein arginine methyltransferases (PRMTs), and histone demethylases (HDMs) (11) in addition to other non-histone epigenetic modifiers. As a result, inhibitors of particularly histone modifying enzymes have been investigated as novel chemotypes in antimalarial drug discovery efforts (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been reported that small molecule HMT inhibitors like BIX‐01294 or its derivative TM2‐115 inhibit the parasite growth at RBC stage . Several BIX‐01294 derivatives were shown to exhibit more selectivity towards parasite HKMTs than host G9a enzyme and efficiently clear parasites at a minimal concentration . Unlike other eukaryotes, the Plasmodium histone methyltransferases are unique in substrate preferences, thus parasite HKMT enzymes can be efficiently targeted through developing ideal small molecules.…”
Section: Introductionmentioning
confidence: 99%